UV Light Activated SnO2/ZnO Nanofibers for Gas Sensing at Room Temperature - Li, Jinze; Gu, Ding; Yang, Yating; Du, Haiying; Li, Xiaogan (Frontiers in Materials, 2019)
Hierarchical SnO2/ZnO nanofiber heterojunctions composed of SnO2 nanofiber matrix on top of which ZnO nanorods protruding 30- 90 nm long were assembled, were examined for chemiresistive-type gas sensors under UV activation at room temperature. The sensor demonstrated excellent sensitivity to different concentrations of formaldehyde and selectivity to several possible interferents such as alcohols, methanol, benzene, methylbeneze and acetone with UV LED at a wavelength of 365 nm. The fiber-like heterojunctions can facilitate the electron transfer from ZnO to SnO2 and this effect would be augmented further under UV light activation. Consequently it enhanced the oxygen adsorptions on the surface of the heterojunctions thus leading to the excellent sensing performance even at room temperature. The influence of the power density and wavelength of UV light used and ambient humidity on the sensor response was systematically investigated. Comparing to the conventional thermal activated one that instead showed preferred response to acetone at 375 oC, the enhanced sensitivity and selectivity of the same sensor at room temperature under LED UV light can be attributed to selective photo-catalytic effect induced by the UV light.